Development of controllino program to integrate the sensor inputs for motors control - Muhammad Shafinaim Akmal, Zulkifli; Ahmad Shahrizan, Abdul Ghani; Mohd Yazid, Abu; Fusaomi, Nagata (Penerbit UMP, 2023)
The system fishcake machine available in the market cannot be controlled by its motor speed based on the desired speed. In addition, this machine uses PLC which causes the production cost of the machine to increase, cannot use components that have a small voltage such as 5V and indirectly makes the PLC a difficult component to integrate all types of components in one PLC only. So, in this paper, we will develop a program using MAXI Automation Controllino for motor speed control that can be changed according to the desired speed with PWM method. In addition, to analyse and validate the integration sensors and motors to control the entire system. Finally, in this study we use Controllino type Maxi Automation to replace the existing PLC in the market and this Controllino will relate to a sensor that is an ultrasonic sensor, infrared range sensor and a DC motor. To control this system, we use a software method that is Arduino IDE to write all the coding. This coding will be written based on all the programs or processes involved in the fishcake machine performed.